PERANCANGAN SISTEM INFORMASI MANAJEMEN PERUSAHAAN “GEN-Z” MENGGUNAKAN METODE AGILE BERBASIS WEBSITE - Ega Bagus Purnama; Germecca Germecca; Niza Aidha Wardhani; Nurul Azizah (The Indonesian Journal of Computer Science Research, 2023)
The development of information technology has had a significant impact on modern companies, affecting the way companies manage information and carry out their operations. In the digital era dominated by generation Z, it is important for companies to adopt an effective and efficient management information system to support their business activities.The purpose of this research is to design a website-based management information system for "Gen-Z" companies using Agile methods. The Agile method was chosen for its flexibility and ability to handle rapidly changing needs in a dynamic business environment.This research will involve the stages of needs analysis, system design, development, implementation, and evaluation. The needs analysis will involve a case study and interviews with stakeholders in the "Gen-Z" company to understand specific business requirements. System design will encompass user interface design, database structure, and system architecture. System development will be carried out iteratively using an Agile approach. The development team will work in short sprints, focusing on developing the most important features that provide direct business value. The system will be implemented as a website accessible to internal users of the "Gen-Z" company through a web browser. System evaluation will involve end-user involvement to assess the effectiveness, usability, and performance of the system. In this phase, user feedback will be collected, and necessary system improvements will be implemented. It is expected that the design of the website-based management information system using the Agile method will provide the "Gen-Z" company with a competitive advantage by improving operational efficiency, information accessibility, and responsiveness to market changes. Additionally, this research can also provide insights and recommendations for other companies looking to adopt Agile methods in developing their management information systems.